Trade credit and the stability of supply chains - Ersahin, Nuri; Giannetti, Mariassunta; Huang, Ruidi (Journal of Financial Economics, 2024)
We show that trade credit flows increase when a firm in a production network becomes a less reliable supplier due to an operating shock. Affected firms extend more trade credit when their customers have lower switching costs or expect more disruption. Suppliers that are more dependent on the affected firms facilitate the trade credit extension. However, when financial constraints at the affected firms and their suppliers prevent the increase in trade credit, customers sever their relationships with the affected firms, and the sales of the affected firms and their suppliers drop, suggesting that trade credit enhances production network stability.